Multi-Carrier Information Hiding Algorithm Based on Angle Structure Descriptor - Shuai Ren (IEEE Access, 2020)
Aiming at the problem that the embedded capacity and security of the single-carrier information hiding algorithm can not be further improved because of the number of carriers, the carrier pre-processing and the embedding of secret information are combined with the image angle structure descriptor, and a multi-carrier information hiding algorithm based on the angle structure descriptor (ASD) is proposed. Firstly, the angle structure descriptors of the extracted image are used to classify the carrier set, and the image angle structure descriptor direction field coding is obtained. Secondly, the secret information is segmented according to the carrier classification number and the preprocessing such as scrambling and optimization is performed. Finally, based on the angle structure the coded data of the feature direction field performs information hiding on a plurality of types of carriers according to the information hiding rule. In particular, the “judgment selection” option is designed during secret information extraction to further improve the performance of the algorithm. The experimental analysis shows that the algorithm has good concealment, strong anti-analysis ability and robustness, and is suitable for applications such as large-capacity secret information covert communication with high security requirements.